SAT0554 Management of Recurrent Pericarditis During Pregnancy: A Rheumatological Approach. (9th June 2015) - Ramoni, V.; Imazio, M.; Pluymaekers, N.; Maestroni, S.; Dicorato, P.; Rampello, S.; Lucianetti, M.; Ghidoni, S.; Valenti, A.; Brucato, A.
Abstract : Background: Pericardial involvement is sporadic during pregnancy and pericarditis is the most common pericardial disease requiring medical therapy. Objectives: The aim was to evaluate the management and outcome of recurrent pericarditis during pregnancy. Methods: The study included 18 pregnancies in 12 women with a history of pericarditis (mean maternal age 31.4 years, mean gestational age 38.82 weeks). These pregnancies were collected in 3 Italian centers from 2002 to 2015. Results: Twelwe pregnancies ended with a live births, two spontaneous abortions occurred within the first ten weeks, one fetal death al 19 TH weeks while 3 pregnancies are ongoing. Corticosteroids were used in twelwe women, nine were also treated with aspirin: six at low dose and continued till delivery, four at high dose; only one continued high dose after gestational week 20. Indomethacin was used in one patient and stopped at gestational week 19; one patient was on colchicine. Five pregnancies were uneventful, in six (33%) recurrences occurred. Recurrences were treated by adding acetaminophen in five cases and ibuprofen in one; in four patients the dose of corticosteroids and aspirin were started/increased. One HELLP syndrome was observed, and one woman experienced mild hypertension and elevation of transaminase. All the infants had a good outcome (mean birth weight 2996g, 6 males). Five recurrences occurred after delivery, three during the puerperium. Conclusions: In women with a history of pericardial diseases, pregnancy should be accurately planned in a period of disease quiescence. Nonselective cyclooxygenase inhibitors and aspirin can be safely used during the first and second trimester but should be withdrawn after gestational week 20 for the risk of ductus constriction. When corticosteroids are needed they are safe when used at low dosages.The effects of colchicine during pregnancy are only studied in patients with familial Mediterranean fever condition in which it appeared to be safe. Nowadays the general outcomes of pregnancies in patients with pericarditis can be similar to the general population, especially when carefully followed by multidisciplinary teams. A rheumatological approach to these pregnancies was safe and effective. References: Imazio M, Brucato A, Belli R, Forno D, Ferro S, Trinchero R, Adler Y. Colchicine for the prevention of pericarditis: what we know and what we do not know in 2014 - systematic review and meta-analysis. J Cardiovasc Med (Hagerstown). 2014 Dec;15(12):840-6.1) Imazio M, Belli R, Brucato A, Cemin R, Ferrua S, Beqaraj F, Demarie D, Ferro S, Forno D, Maestroni S, Cumetti D, Varbella F, Trinchero R, Spodick DH, Adler Y. Efficacy and safety of colchicine for treatment of multiple recurrences of pericarditis (CORP-2): a multicentre, double-blind, placebo-controlled, randomised trial. Lancet. 2014 Jun 28;383(9936):2232-7. Imazio M, Brucato A, Adler Y. A randomized trial of colchicine for acute pericarditis. N Engl J Med. 2014 Feb 20;370(8):781. Imazio M, Spodick D.H., Brucato A., Trinchero R., Adler Y. Controversial issue in the management of pericardial disease. Circulation. 2010; 121: 916-928. Disclosure of Interest: None declared